Development of Augmented Reality Book Learning Media Based on Assemblr Edu on Body Organs Material in Elementary Schools - Rizqiyah, Anifatur; Sriwijayanti, Ribut Prastiwi; Jannah, Faridahtul (EduBase : Journal of Basic Education, 2024)
Purpose: This research aims to develop an Augmented Reality Book based on Assemblr Edu as teaching material to support science learning, Body Organs material for class V students, which is still not available because the material contains abstract concepts and makes it difficult for students to understand science learning. Methods: The type of research used is Research and Development (R&D) with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. This research was carried out in class V of SDN Curahgrinting 3 Probolinggo. 4 class V students were tested on a small scale and 14 class V students of SDN Curahgrinting 3 Probolinggo were tested on a large scale. The instruments used in the research were validation questionnaires from material science experts and media experts as well as pretest and posttest. Results: The results of the research and development that have been carried out obtained (1) the percentage of validation scores for science material experts of 89% with revisions according to suggestions and (2) the percentage of validation scores for media experts of 93% with revisions according to suggestions. These results show that the level of validity of the book developed is declared very valid. The teacher response score percentage results were 94% and the student response test results were: (1) Small scale tests were 89% with very good criteria, and (2) Large scale tests were 93% with very good criteria. criteria, thus the Augmented Reality Book is very good. good for use in learning. The pretest and posttest results show that the Augmented Reality Book learning media based on Assemblr Edu is effective, this is proven by the fact that all class V students can be said to have completed with a percentage of 100% after studying with the Augmented Reality Book media and obtaining the Minimum Completeness Criteria (KKM) score. Conclusion: Augmented Reality Book learning media based on Assemblr Edu Body Organs is stated to be very suitable for use in the classroom learning process and can increase motivation and stimulate student learning activities. The implication is that the use of this learning media can increase student motivation, deepen understanding of concepts, and facilitate the development of technological and collaborative skills.